2018
DOI: 10.3390/ma11060897
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Carrier Solvents for Pigments Extracted from Spalting Fungi

Abstract: The use of both naturally occurring and synthetic pigmented wood has been prevalent in woodcraft for centuries. Modern manifestations generally involve either woodworkers’ aniline dyes, or pigments derived from a special class of fungi known as spalting fungi. While fungal pigments are more renewable than anilines and pose less of an environmental risk, the carrier required for these pigments—dichloromethane (DCM)—is both problematic for humans and tends to only deposit the pigments on the surface of wood inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The pigment can be incorporated in water-reliant processes such as the mat-forming stage in the paper manufacturing process [8], which allows for utilization in an array of industrial practices. Further testing will be required on paper quality after dyeing and the effects of the solvents, but previous research showed that the pigment generated by S. cuboideum can be carried in other types of solvents if necessary [37].…”
Section: Discussionmentioning
confidence: 99%
“…The pigment can be incorporated in water-reliant processes such as the mat-forming stage in the paper manufacturing process [8], which allows for utilization in an array of industrial practices. Further testing will be required on paper quality after dyeing and the effects of the solvents, but previous research showed that the pigment generated by S. cuboideum can be carried in other types of solvents if necessary [37].…”
Section: Discussionmentioning
confidence: 99%
“…An important factor relies in previous studies on potential solvent carriers for the pigment from spalting fungi such as [41] as it is possible to use other solvents such as acetonitrile that can replace DCM. In the specific case of the pigment from S. cuboideum it is possible to obtain the dramada crystals in high purity with the use of acetone [38].…”
Section: Color Coveragementioning
confidence: 99%
“…A less potentially hazardous carrier is needed for these pigments to be utilized by consumers. Numerous attempts have been made to carry these spalting pigments in less toxic solvents, none of which have had success across all three major colors [ 27 ]. This has led to the investigation into using oils as carriers for the pigments [ 28 , 29 ], as natural oils have historic uses in textiles, especially in waterproofing applications.…”
Section: Introductionmentioning
confidence: 99%